PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI ANIMEKER BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN BAHASA INDONESIA - Masnunah; Miftachul Jannah Azwajah; Juaidah Agustina (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to develop problem-based learning animaker animation video learning media on official letter material in grade VII of junior high school and also aims to determine the level of application and reliability of animation video educational resources. Analysis, Design, Development, and Implementation are the four stages of the ADDIE model, which is the basis for the type of development research being applied. The very valid category received an average score of 88% based on the results of the material expert validation assessment. An average score of 87% was obtained in the median's validation assessment, with the category being very valid. At the implementation stage, the trial was carried out 2 times, the first was a small-scale test conducted on 5 students who obtained a percentage of 88% with a very practical category, while in a large-scale test conducted by 26 students obtained a percentage of 85% with a practical category. Thus, it can be concluded that the learning media of animaker animation videos based on problem-based learning in the official letter material of grade VII junior high school is suitable for use in the learning process.